2015
DOI: 10.1016/j.tvjl.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of ABC transporter expression in canine multicentric lymphoma

Abstract: Background: A genetic predisposition for certain tumour types has been proven for some dog breeds. Some studies have suggested that this may also be true for the Golden retriever breed. The present study aimed to examine a possible existence of a tumour (type) predisposition in the Dutch population of Golden retrievers by evaluating annual estimated incidence rates compared to incidence rates from previous publications. A second aim was to evaluate whether incidences of various tumours differed as related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 76 publications
1
63
0
2
Order By: Relevance
“…It has generally been thought that lymphomas in humans and dogs acquire multidrug resistance from the continuous activation of drug transporters, such as ABCB1 and ABCG2, after long-term exposure to anticancer drugs, inducing chemical tolerance in the patient [3, 27]. Interestingly, we have shown here that mild hypoxic stimulation also reduced the sensitivity to DOX of DOX-resistant lymphoma cells generated with conventional methods.…”
Section: Discussionsupporting
confidence: 50%
“…It has generally been thought that lymphomas in humans and dogs acquire multidrug resistance from the continuous activation of drug transporters, such as ABCB1 and ABCG2, after long-term exposure to anticancer drugs, inducing chemical tolerance in the patient [3, 27]. Interestingly, we have shown here that mild hypoxic stimulation also reduced the sensitivity to DOX of DOX-resistant lymphoma cells generated with conventional methods.…”
Section: Discussionsupporting
confidence: 50%
“…Finally, T‐cell phenotype appeared to predominate, which may have contributed to the poor chemotherapy response observed; intrinsic drug resistance is common with this form and is associated with increased ABCG2 expression (Zandvliet et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…They found that dogs with T cell lymphoma had higher intrinsic drug resistance than dogs with B cell lymphoma and dogs with drug resistant T cell lymphoma had increased ABCG2 mRNA expression. ABCG2 plays a role in transport and cellular sensitivity to doxorubicin and has been associated with doxorubicin resistance in humans . These findings suggest that dogs with T cell lymphoma are less sensitive to doxorubicin and require non‐doxorubicin‐based protocols for the treatment of this disease.…”
Section: Introductionmentioning
confidence: 92%